Debt, Profit, and Tax: Investigating Corporate Tax Behavior - Adijaya, Vincent; Endro Dwi Radianto, Wirawan (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
In the past few years, tax avoidance has been a key concern and has drawn the focus of the Indonesian government. Tax avoidance causes harm to the country’s tax revenue, which affects government program financing and infrastructure development. The purpose of this study is to examine the influence of financial distress, profitability, and leverage on tax avoidance among property and real estate firms listed on the Indonesia Stock Exchange during 2019-2023. The data used is collected from the company’s financial statements, available on their official websites. This study's results show that financial distress has a significant positive impact on tax avoidance, suggesting that distressed firms tend to adopt aggressive tax avoidance to manage their financial challenges. Otherwise, leverage has a significant negative impact on tax avoidance. The reason is that companies with greater leverage face tighter supervision from creditors and outsiders, which can restrict their engagement in aggressive tax avoidance. Additionally, debt obligations may drive companies to focus more on tax compliance to avoid potential legal and financial repercussions. ROA does not show a significant impact on tax avoidance. The results of this study support agency theory, which emphasizes that external pressures, such as debt obligations and stable financial conditions, reduce managers' tendency to engage in opportunistic actions like tax avoidance. The study offers implications for stakeholders to focus more on internal financial factors and capital structure when overseeing corporate tax compliance.